A Randomized, Single‐Blind, Placebo‐Controlled, 3‐Way Crossover Study to Evaluate the Effect of Therapeutic and Supratherapeutic Doses of Edaravone on QT/QTc Interval in Healthy Subjects. Issue 1 (15th June 2020) - Shimizu, Hidetoshi; Inoue, Shinsuke; Endo, Mai; Nakamaru, Yoshinobu; Yoshida, Kaori; Natori, Tomoko; Kakubari, Masae; Akimoto, Makoto; Kondo, Kazuoki
Abstract: This randomized, single‐blind, 3‐way crossover study assessed the effect of edaravone on QT interval, including an exposure‐response analysis. Twenty‐seven healthy Japanese male volunteers, aged 20 to 49 years, were randomly assigned to receive a single intravenous dose of each treatment in 1 of 3 sequences (n = 9 each): ACB, BAC, and CBA, where A was edaravone 60 mg (therapeutic dose), B was edaravone 300 mg (supratherapeutic dose), and C was normal saline (placebo). Electrocardiographs were collected to assess treatment effects. In an exposure‐response analysis, a linear model was determined to be valid and indicated no statistically significant positive slope for the relationship between change from baseline in QTcF (ΔQTcF) and edaravone concentration (0.000155 ms/(ng/mL); P = .1478); upper bounds of 2‐sided 90% confidence intervals after placebo adjustment (ΔΔQTcF) were <10 milliseconds at the geometric mean maximum concentration for each edaravone dose. Overall estimated values by time point of ΔΔQTcF ≤0.9 milliseconds, no outlier values, and no morphologic changes suggestive of repolarization abnormalities were observed. Analysis of heart rate, PR interval, and QRS duration also revealed no adverse findings. These data indicate that edaravone, even at supratherapeutic doses, does not produce clinically meaningful QT prolongation and has no clinically relevant cardiac effects.